Circulating microRNAs are new and sensitive biomarkers of myocardial infarction - D'Alessandra, Yuri (Oxford University Press, 2010)
AIMS: Circulating microRNAs (miRNAs) may represent a novel class of biomarkers; therefore, we examined whether acute myocardial infarction (MI) modulates miRNAs plasma levels in humans and mice. METHODS AND RESULTS: Healthy donors (n = 17) and patients (n = 33) with acute ST-segment elevation MI (STEMI) were evaluated. In one cohort (n = 25), the first plasma sample was obtained 517 ± 309 min after the onset of MI symptoms and after coronary reperfusion with percutaneous coronary intervention (PCI); miR-1, -133a, -133b, and -499-5p were ∼15- to 140-fold control, whereas miR-122 and -375 were ∼87–90% lower than control; 5 days later, miR-1, -133a, -133b, -499-5p, and -375 were back to baseline, whereas miR-122 remained lower than control through Day 30. In additional patients (n = 8; four treated with thrombolysis and four with PCI), miRNAs and troponin I (TnI) were quantified simultaneously starting 156 ± 72 min after the onset of symptoms and at different times thereafter. Peak miR-1, -133a, and -133b expression and TnI level occurred at a similar time, whereas miR-499-5p exhibited a slower time course. In mice, miRNAs plasma levels and TnI were measured 15 min after coronary ligation and at different times thereafter. The behaviour of miR-1, -133a, -133b, and -499-5p was similar to STEMI patients; further, reciprocal changes in the expression levels of these miRNAs were found in cardiac tissue 3–6 h after coronary ligation. In contrast, miR-122 and -375 exhibited minor changes and no significant modulation. In mice with acute hind-limb ischaemia, there was no increase in the plasma level of the above miRNAs. CONCLUSION: Acute MI up-regulated miR-1, -133a, -133b, and -499-5p plasma levels, both in humans and mice, whereas miR-122 and -375 were lower than control only in STEMI patients. These miRNAs represent novel biomarkers of cardiac damage.